2020
DOI: 10.1111/gean.12264
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Spatiotemporal Clusters by Means of Agglomerative Hierarchical Clustering and Bayesian Regression Analysis with Spatiotemporally Varying Coefficients: Methodology and Application to Dengue Disease in Bandung, Indonesia

Abstract: Dengue disease has serious health and socioeconomic consequences. Preventive actions are needed to avoid outbreaks. Bayesian spatiotemporal models with conditional autoregressive (CAR) and random walk (RW) priors are two common smoothing approaches used in disease mapping to develop early warning systems and action plans. However, this approach can lead to over-smoothing, such that discontinuities in the risk surface are "averaged" out. Moreover, local variation in the relationship between disease risk and spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 122 publications
5
41
0
Order By: Relevance
“…The expected rate is calculated using external standardization. It is defined based on the overall average across all areas and periods (Abente et al 2018 ; Jaya and Folmer 2020 , 2021a , b ): …”
Section: The Spatiotemporal Generalized Geoadditive-gaussian Field Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The expected rate is calculated using external standardization. It is defined based on the overall average across all areas and periods (Abente et al 2018 ; Jaya and Folmer 2020 , 2021a , b ): …”
Section: The Spatiotemporal Generalized Geoadditive-gaussian Field Modelmentioning
confidence: 99%
“…Following Moraga et al ( 2017 ), Jaya and Folmer ( 2020 , 2021a , b ), and Utazi et al ( 2019 ), we model the relative risk as a non-separable Poisson log-linear model as follows 6 : …”
Section: The Spatiotemporal Generalized Geoadditive-gaussian Field Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…with λ taken to be 1 (Fahrmeir & Kneib, 2011) (d) The combination of inverse distance and fixed distance nearest neighbor distance. We evaluated the spatial weights matrices W for Model M4 using the following model selection criteria: the deviance information criterion (DIC), the Watanabe-Akaike information criterion (WAIC), the marginal predictive likelihood (MPL), mean absolute error (MAE), the root mean square error (RMSE), the correlation between observed and predicted values (r), and the spatiotemporal Moran I statistic (MoranST) for residual spatiotemporal autocorrelation (see Jaya and Folmer (2020b) for details on the MoranST). We ran the 15 models in INLA, and report the results in Table B5.…”
Section: B2 Comparison Spatial Weights Matricesmentioning
confidence: 99%
“…In this, all the stored observations make their cluster and merge until all similar information cluster in one. Several recent (Hu et al, 2019;Jaya et al, 2020) studies have used this clustering and indicated that this method is much easier to utilize. Some important applications using the clustering method were discussed in Bouguettaya et al 2015.…”
Section: Cluster Analysismentioning
confidence: 99%